O whatsapp no Extra (RJ) e no Diário Gaúcho (RS) : a participação da audiência na reconfiguração do processo de produção da notícia - Specht, Patrícia Pivoto (2019)
The present thesis analyzes the impact in news production of conversations established through WhatsApp message exchanges between the readers and the newspaper offices of Diário Gaúcho, of Porto Alegre (RS), and Extra, from Rio de Janeiro (RJ), in view of three main objectives: to understand the impact of exchanging messages in three stages of news production, established as a guideline, determination and published news, to define the characteristics of the relations and to critically point out limitations and possibilities of the interactivity systems implanted in newspapers. For this purpose, we conducted research of ethnographic nature based on participant observation in the two newsrooms, allied to interviews with professionals of the communication outlets. Among the conclusions reached, it was evident that most of the content produced from the audience-writing relationship through WhatsApp results in agenda, but the reader's interference and dialogues established at other stages of the process have the potential to qualify the news, especially regarding dynamic work in progress with the target audience and being able to collaborate in updating and improving journalistic coverage. Among the limitations found in the systems implemented, are the lack of investment in personnel and the absence of collaborative coverage.